Role of Exogenous Melatonin, Hydrogen Sulfide and Nitric Oxide on Organic Acid Content of Eruca sativa L. under Salt Stress (International Journal of Scientific Research and Management (IJSRM), 2021)
Salt stress affects agricultural output by influencing numerous internal metabolisms in plants and disrupting physiological and biochemical activities such as photosynthesis, translocation, respiration, and growth stimulants. The role of exogenous melatonin, hydrogen sulfide and nitric oxide application on the organic acid contents of rocket plants under salt stress was examined in this study. Different salt doses (0, 150 and 250 mM NaCl) and exogenous applications (0, 50 and100 µM) were made to rocket plants under the greenhouse conditions. Plants leaves and roots exhibited a decline in the organic acid contents under salinity stress. Application of the amendments, however, was found significant in mitigating the negative effect of salt stress. Melatonin and hydrogen sulfide treatments had a stronger anti-salt action in the leaves. On the other hand, nitrous oxide role was more obvious in the roots followed by melatonin. With this, exogenous applications to the plant mitigated the harmful effects of salt stress on organic acid contents depending on the dose.